Penerapan Metode Multi Attribute Utility Theory (MAUT) Dalam Pemilihan Karyawan yang di Non-Aktifkan di Masa Pandemi - Juanda Hakim Lubis; Shinta Esabella; Mesran Mesran; Desyanti Desyanti; Deby Monalisa Simanjuntak (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Coronavirus Disease 2019 (Covid-19) was first discovered in China, spread to various countries including Indonesia in March 2020. Until 2021 Covid-19 has not disappeared. This of course has an impact that can harm the country and society. Therefore, the government made a policy of Large-Scale Social Restrictions (PSBB) with the aim of breaking the chain of the spread of Covid-19. One of the impacts felt by the community with its presence is the deactivation of employees carried out by several companies to workers on the grounds that they do not have the money to pay the workers. PT. XYZ has difficulty choosing which employees to deactivate. This research is based on these reasons, so the authors decided to use the Multi Attribute Utility Theory (MAUT) method to help make decisions to choose employees who deserve to be deactivated with job prospects, age, length of work per year, education, dependents with an alternative number of 10 (Ten) ) employees. The use of the MAUT method is expected to determine the criteria for employees who deserve to be deactivated, because the MAUT method will perform a ranking process based on attributes with different weights so that the results are more optimal, then a ranking process will be carried out which will determine the optimal alternative as well. The 5 (five) alternatives that deserve to be deactivated are A2 with a result of 0,9303, A8 with a result of 0,5561, A4 with a result of 0,533, A9 with a result of 0,4978, and A1 with a result of 0,4867 is 5 a viable alternative to deactivate during the pandemic